Health screening for women with physical disability in Australian general practice: A survey. Issue 2 (April 2019) - Halcomb, Elizabeth J.; Peters, Kath; Smyth, Elizabeth
Abstract: Background: Early detection of gynaecological issues improves health outcomes and reduces mortality. Such early detection is best achieved via regular, proactive health screening. Like other disadvantaged groups, women with physical disability have much lower gynaecological screening rates than the general population. Aim: The aim of this paper is to explore the current role of general practice nurses in women's health screening for individuals with physical disability. Methods: A national online survey of Australian general practice nurses was conducted. Findings: One hundred and seventy-eight general practice nurses completed the survey. Sixty-one percent reported having experience in working with people with a physical disability. Around one third of participants reported having completed specific education about physical disability. Most general practices implemented strategies to facilitate physical access for those with disability. However, few general practices had a medical records system that enabled identification of physical disability. Thirty-seven participants reported providing women's health screening for 89 women with a physical disability in the 4 weeks prior to the survey. A range of strategies were used to support women during these screening procedures. These could be broadly classified into; a) providing practical assistance to facilitate screening, and b) modifying technique and positioning for comfort. Conclusions: The limited experience with disability amongst an experienced nursing cohort, and the difficulty inherent in identifying those with a disability within recall and reminder systems, adds complexity to the provision of screening for women with a disability. Whilst participants articulated some innovative and creative strategies to assist women with a disability during health screening, enhanced awareness amongst nurses and proactive strategies would likely enhance service accessibility in this vulnerable group.